Effect of Radial Density Configuration on Wave Field and Energy Flow in Axially Uniform Helicon Plasma - 苌磊 李庆冲 张辉洁 李应红 吴云 张百灵 庄重 (Plasma science & technology, 2016)
The effect of the radial density configuration in terms of width, edge gradient and volume gradient on the wave field and energy flow in an axially uniform helicon plasma is studied in detail. A three-parameter function is employed to describe the density, covering uniform,parabolic, linear and Gaussian profiles. It finds that the fraction of power deposition near the plasma edge increases with density width and edge gradient, and decays in exponential and ＂bumpon-tail＂ profiles, respectively, away from the surface. The existence of a positive second-order derivative in the volume density configuration promotes the power deposition near the plasma core, which to our best knowledge has not been pointed out before. The transverse structures of wave field and current density remain almost the same during the variation of density width and gradient, confirming the robustness of the m=1 mode observed previously. However, the structure of the electric wave field changes significantly from a uniform density configuration, for which the coupling between the Trivelpiece-Gould（TG） mode and the helicon mode is very strong, to non-uniform ones. The energy flow in the cross section of helicon plasma is presented for the first time, and behaves sensitive to the density width and edge gradient but insensitive to the volume gradient. Interestingly, the radial distribution of power deposition resembles the radial profile of the axial component of current density, suggesting the control of the power deposition profile in the experiment by particularly designing the antenna geometry to excite a required axial current distribution.